Evaluation of the Immunogenic Response of a Novel Enterobactin Conjugate Vaccine in Chickens for the Production of Enterobactin-Specific Egg Yolk Antibodies - Zeng, Ximin; Wang, Huiwen; Huang, Canghai; Logue, Catherine M.; Barbieri, Nicolle L.; Nolan, Lisa K.; Lin, Jun (Frontiers in Immunology, 2021)
Passive immunization with specific egg yolk antibodies (immunoglobulin Y, IgY) is emerging as a promising alternative to antibiotics to control bacterial infections. Recently, we developed a novel conjugate vaccine that could trigger a strong immune response in rabbits directed against enterobactin (Ent), a highly conserved siderophore molecule utilized by different Gram-negative pathogens. However, induction of Ent-specific antibodies appeared to be affected by the choice of animal host and vaccination regimen. It is still unknown if the Ent conjugate vaccine can trigger a specific immune response in layers for production of anti-Ent egg yolk IgY. In this study, three chicken vaccination trials were performed to determine conditions for efficient production of anti-Ent egg yolk IgY. Purified Ent was conjugated to three carrier proteins, keyhole limpet hemocyanin (KLH), bovine serum albumin (BSA) and CmeC (a subunit vaccine candidate), respectively. Intramuscular immunization of Barred Rock layers with KLH-Ent conjugate four times induced strong immune response against whole conjugate vaccine but the titer of Ent-specific IgY did not change in yolk with only a 4 fold increase detected in serum. In the second trial, three different Ent conjugate vaccines were evaluated in Rhode Island Red pullets with four subcutaneous injections. The KLH-Ent or CmeC-Ent conjugate consistently induced high level of Ent-specific IgY in both serum (up to 2,048 fold) and yolk (up to 1,024 fold) in each individual chicken. However, the Ent-specific immune response was only temporarily and moderately induced using a BSA-Ent vaccination. In the third trial, ten White Leghorn layers were subcutaneously immunized three times with KLH-Ent, leading to consistent and strong immune response against both whole conjugate and the Ent molecule in each chicken; the mean titer of Ent-specific IgY increased approximately 32 and 256 fold in serum and yolk, respectively. Consistent with its potent binding to various Ent derivatives, the Ent-specific egg yolk IgY also inhibited in vitro growth of a representative Escherichia coli strain. Together, this study demonstrated that the novel Ent conjugate vaccine could induce strong, specific, and robust immune response in chickens. The Ent-specific hyperimmune egg yolk IgY has potential for passive immune intervention against Gram-negative infections.